KEBUTUHAN RUANG TERBUKA HIJAU (RTH) DI KOTA PEKANBARU - Fitrah Parlindungan; Mubarak Mubarak; Imam Suprayogi (Jurnal Ilmu Lingkungan, 2018)
The development of urban progress often experiences an inconsistency between urban development needs and the availibility and needs of RTH. Pekanbaru city turned into a city that moves into a form of metropolitan city, land use change in Pekanbaru City causes enviromental quality degradation, so that the existing area of existing public RTH must be considered and expanded and intensified its function. This study aims to determine the extent of public RTH that has existed until 2017 in the city of Pekanbaru and how to distribute the RTH and review the results of the strategy analysis of achieving the availibilty and needs of RTH in the city of Pekanbaru. The research was conducted in March to July 2017. The results showed that the proportion of RTH was set at least 30% of the total area of Pekanbaru City which is 18,967.80 ha consisting of Public RTH 12,645.20 ha (20%) and Private RTH 6,322,60 ha (10%) as mandated by Law No. 26 of 2007. The existing area of public RTH in Pekanbaru City in 2017 has only reached 419.70 ha (2.21%) and there is still a shortage of public RTH covering an area of 12,225.50 ha. Public RTH located in Pekanbaru City until 2017 consists of : (1) City Park covering an area of 98,522.02 m2, (2) Urban Forest covering an area of 1,698,900 m2, (3) Green Road RTH with an area of 161,001.86 m2, (4 ) Lake RTH covering an area of 1,201,100.00 m2, (5) Funeral RTH covering an area of 318,200.00 m2, (6) Sports Field RTH covering an area of 505,651.48 m2 and (7) RTH located in Government assets covering 213,657.20 m2. The Pekanbaru City Government and Pekanbaru City DPRD need to immediately place the green space problem as an important issue in the budget and ongoing program discussion and the Pekanbaru City Government must increase the availability of the budget for public green open space in an effort to achieve 20%. The plan to develop RTH in Pekanbaru City will be realized through the utilization of potential areas around the City of Pekanbaru. The realizationof the RTH of Pekanbaru City which is the Capital of Riau Province revealed in the RTH masterplan of at least 30% can be arranged in a systematic and realistic program indication framework.